Optimisation of Belarusian tourism platforms aimed at acquiring Chinese tourists - Yanyan, Zhai; Karachun, Irina A.; Hui, Chang (Journal of the Belarusian State University. Economics, 2023)
The development of the tourism economics in Belarus is an important part of the national sustainable development strategy. As once the largest tourist outbound country, China is expected to increase the number of Belarusian inbound tourists and to improve the level of inbound tourism consumption. At present, Belarus has taken numerous measures to give it an advantage in acquiring Chinese tourists. In order to further attract Chinese tourists, the optimisation of the Belarusian tourism platforms provides possible solutions. The authors of the article use the comparative analysis method to study the relative strengths and weaknesses of Belarusian tourism platforms. Then they analyse the new travel trends and dilemmas of Chinese tourists. Strategies for Belarusian tourism platform optimisation include promoting the integration and improvement of the ecosystem, promoting the innovation of production methods for the co-creation of tourist value, and promoting the innovation of business models. Finally, the effectiveness of Belarus tourism platform optimisation on the economics is concluded.
Keywords: tourism platform; Belarus; Chinese tourists; optimisation